Understanding Mens Rea in command responsibility: from Yamashita to Blas╠åkić and beyond - Martinez, Jenny S. (Journal of international criminal justice, 2007)
Despite 50 years of doctrinal evolution, the mens rea for command responsibility is still unclear. Four factors help explain this. First, international courts frequently borrow mens rea terminology from national legal systems without adequately understanding or explaining differences in how those terms are used. Second, courts and commentators often neglect to engage explicitly in an element-by-element analysis of mens rea requirements, simply (and wrongly) assuming that the same mental state must apply to each element of an offence. Third, courts sometimes react to evidentiary uncertainty by creating legal uncertainty. Finally, courts have responded to normative criticism of command responsibility doctrine in its more expansive versions, but have been unwilling to explore the normative arguments in favour of it. Normative arguments about command responsibility doctrine must take account of differences between ordinary municipal criminal law and international criminal law, including the origins of command responsibility in the laws of war, and the special factual contexts in which it is applied. The article argues that there is solid (though not incontrovertible) support in customary international law for holding superiors liable when they culpably fail to acquire knowledge of their subordinates misdeeds, and that there are strong retributive and utilitarian arguments for such an approach. International courts should adopt such a duty of knowledge standard